2012
DOI: 10.1042/bj20111166
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of hydroperoxyeicosatetraenoic acids to their hydroxy derivatives by apolipoprotein D: implications for lipid antioxidant activity and Alzheimer's disease

Abstract: ApoD (apolipoprotein D) is up-regulated in AD (Alzheimer's disease) and upon oxidative stress. ApoD inhibits brain lipid peroxidation in vivo, but the mechanism is unknown. Specific methionine residues may inhibit lipid peroxidation by reducing radical-propagating L-OOHs (lipid hydroperoxides) to non-reactive hydroxides via a reaction that generates MetSO (methionine sulfoxide). Since apoD has three conserved methionine residues (Met(49), Met(93) and Met(157)), we generated recombinant proteins with either one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 52 publications
9
89
0
6
Order By: Relevance
“…The same phenomenon has been observed in several cellular models where it has been shown that some stress conditions activate Apo D expression and induce Apo D mRNA accumulation (Do Carmo et al, 2002;He et al, 2009). In this sense, Apo D has been suggested as a neuroprotective protein that may be part of an antioxidant defense system (Do Carmo et al, 2007;Ganfornina et al, 2008), playing an evolutionary and crucial role in response to oxidative stress with a beneficial function mediated by the control of peroxide lipids (He et al, 2009) or directly by intrinsic antioxidant properties (Bhatia et al, 2011;Kim et al, 2009;Oakley et al, 2012;Zhang et al, 2010). Do Carmo et al (2007), using immortalized astrocytes and a hepatic cell line, found that growth arrest and lipopolysaccharide, a proinflamatory agonist, cause a subcellular accumulation of Apo D protein in the cytoplasm that is followed by its displacement to the cellular extensions and nucleus, where they proposed that it may modulate transduction signal pathways and some nuclear processes.…”
Section: Discussionmentioning
confidence: 63%
“…The same phenomenon has been observed in several cellular models where it has been shown that some stress conditions activate Apo D expression and induce Apo D mRNA accumulation (Do Carmo et al, 2002;He et al, 2009). In this sense, Apo D has been suggested as a neuroprotective protein that may be part of an antioxidant defense system (Do Carmo et al, 2007;Ganfornina et al, 2008), playing an evolutionary and crucial role in response to oxidative stress with a beneficial function mediated by the control of peroxide lipids (He et al, 2009) or directly by intrinsic antioxidant properties (Bhatia et al, 2011;Kim et al, 2009;Oakley et al, 2012;Zhang et al, 2010). Do Carmo et al (2007), using immortalized astrocytes and a hepatic cell line, found that growth arrest and lipopolysaccharide, a proinflamatory agonist, cause a subcellular accumulation of Apo D protein in the cytoplasm that is followed by its displacement to the cellular extensions and nucleus, where they proposed that it may modulate transduction signal pathways and some nuclear processes.…”
Section: Discussionmentioning
confidence: 63%
“…A very important study recently identified Apolipoprotein D (ApoD), an extracellular lipid-binding lipoprotein, as having a lysosomal membrane stabilising function (Pascua-Maestro et al, 2017). ApoD can reduce radical-propagating lipid hydroperoxides (Bhatia et al, 2012) and was shown to be endocytosed and to inhibit lysosomal lipid peroxidation in vitro (Pascua-Maestro et al, 2017). The authors suggested that ApoD could play an important role in the brain by protecting neurones against oxidative damage and could have important implications in neurodegenerative disorders (Pascua-Maestro et al, 2017).…”
Section: Oxidised Protein Removal From the Cytoplasm Nucleus And Endmentioning
confidence: 99%
“…ApoD is known to be upregulated in the brains of patients with Alzheimer disease, and apoD aggregates were detected in the hippocampus of patients with Alzheimer disease. 7 In other studies, it was shown that overexpression in mouse brain of human apoD prevented the increase in brain lipid peroxides after oxidant treatment and improved survival; the loss of apoD had the opposite effect. 9 ApoD is carried in the plasma mainly on HDLs.…”
Section: Circulation Research December 6 2013mentioning
confidence: 96%
“…7,8 Treatment of apoD with hydroperoxyeicosatetraenoic acids resulted in loss of one-third of the methionine residues in apoD and was accompanied by the formation of methionine sulfoxide and resulted in protein aggregation. ApoD is known to be upregulated in the brains of patients with Alzheimer disease, and apoD aggregates were detected in the hippocampus of patients with Alzheimer disease.…”
Section: Circulation Research December 6 2013mentioning
confidence: 99%
See 1 more Smart Citation